2016
DOI: 10.1177/0022343316659334
|View full text |Cite
|
Sign up to set email alerts
|

How can political trust be built after civil wars? Evidence from post-conflict Sierra Leone

Abstract: As a fundamental concept in peace research, trust, or the lack of it, has shown to be associated with the onset of violent conflict, the instability of negotiated settlement, and the sustainability of peace. Despite its proven importance, the question of how political trust can be built after civil conflicts has only received limited attention and remains unanswered. While previous studies demonstrated that improved provision of public services plays a significant role in a trust-building process, the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 63 publications
2
18
0
Order By: Relevance
“…Based on research in post-conflict Sierra Leone, it is suggested that being responsive to the needs of people is the key to successful trust building. National governments must demonstrate real concern for the needs of local people and engage them in policy making in order to enhance political trust [54]. Good governance, locally, as defined as a decrease in political corruption, and increased trust in politicians and political performance, is associated with a lower probability of conflict-related violence at the subnational level [55].…”
Section: Discussionmentioning
confidence: 99%
“…Based on research in post-conflict Sierra Leone, it is suggested that being responsive to the needs of people is the key to successful trust building. National governments must demonstrate real concern for the needs of local people and engage them in policy making in order to enhance political trust [54]. Good governance, locally, as defined as a decrease in political corruption, and increased trust in politicians and political performance, is associated with a lower probability of conflict-related violence at the subnational level [55].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, rather than becoming embroiled in a debate about whether trust in government is culturally or institutionally based (e.g. see Mishler and Rose, 2001; Wong, 2016), we allowed our research participants to make connections, in line with our exploratory approach.…”
Section: Research Question and Methodologymentioning
confidence: 99%
“…As Wong (2016) notes, ‘Trust development is an evolutionary process that involves constant evaluation and learning about the behaviours of the trustees’ (p. 2). Through public communication and public relations activities, citizens are able to make such judgements about political actors, and this in turn affects how they engage with the democratic process (Brunner and Smallwood, 2019; Hargie and Irving, 2017).…”
Section: Public Relations Elite Discourse Peace and Conflictmentioning
confidence: 99%
See 1 more Smart Citation
“…In considering these questions, we engage with a small but growing body of research on the social legacies of violence in regions recovering from conflict (e.g. Kijewski and Freitag (2016); Mironova and Whitt (2016); Wong (2016)). This literature o↵ers two competing perspectives.…”
Section: Introductionmentioning
confidence: 99%